Great White Shark - Ellis, Richard and McCosker, John E (California Stanford University Press, 1991)
This is an account for general readers of everything that is known about the great white shark, the most feared creature in the world's oceans. It is based on extensive research into the scientific literature and lore of this well-adapted predator and on analysis of historical records.
Include Color Illustration, Bibliography and Index
Keywords: White shark